GLOBALISASI DAN PERIKLANAN: PENAMPILAN BUDAYA ASING DALAM IKLAN INDONESIA - Rumyeni ' (Universitas Riau, 2012)
Globalization and Advertising: Foreign Cultural Performance in Advertising Indonesia.This study aims to determine how the appearance of foreign cultural elements in advertising Indonesia. Toachieve the goal of qualitative content analysis method used in this study. A total of two advertising CocaCola and Sprite have analyzed the two ads. The theory of cultural imperialism is used as a guide inanalyzing the phenomenon of the appearance of foreign cultures in this study. The results of this studyindicate that the Coca Cola and Sprite ads featuring many foreign cultures.